Novel pathogenic variants of DNAH5 associated with clinical and genetic spectra of primary ciliary dyskinesia in an Arab population - Al-Mutairi, Dalal A.; Alsabah, Basel H.; Pennekamp, Petra; Omran, Heymut (Frontiers in Genetics, 2024)
Introduction: Primary ciliary dyskinesia (PCD) is caused by dysfunction of motile cilia resulting in insufficient mucociliary clearance of the lungs. The aim of this study is to map novel PCD variants and determine their pathogenicity in PCD patients in Kuwait. Methods: Here we present five PCD individuals belonging to a cohort of 105 PCD individuals recruited from different hospitals in Kuwait. Genomic DNA from the family members was analysed to screen for pathogenic PCDvariants. Transmission electron microscopy (TEM) and immunofluorescence (IF) analyses were performed on nasal biopsies to detect specific structural abnormalities within the ciliated cells. Results: Genetic screening and functional analyses confirmed that the five PCD individuals carry novel pathogenic variants in DNAH5 that cause PCD in three Arabic families; One multiplex family with two affected individuals has two novel homozygous missense variants in DNAH5 causing PCD with situs inversus. Another multiplex family with two affected individuals has two newly identified compound heterozygous variants in DNAH5 causing PCD with situs solitus. In addition, novel heterozygous variants were identified in a child with PCD and situs solitus from a singleton family with unrelated parents. TEM analysis demonstrated a lack of outer dynein arms (ODA) in all analysed samples. IF analysis confirmed absence of dynein arm component DNAH5 from the ciliary axoneme. Conclusions: Newly identified pathogenic variants in DNAH5 are associated with PCD with variable pulmonary clinical manifestations in Arabic families.